2015
DOI: 10.1051/0004-6361/201526291
|View full text |Cite
|
Sign up to set email alerts
|

Lines and continuum sky emission in the near infrared: observational constraints from deep high spectral resolution spectra with GIANO-TNG

Abstract: Aims. Determining the intensity of lines and continuum airglow emission in the H-band is important for the design of faint-object infrared spectrographs. Existing spectra at low/medium resolution cannot disentangle the true sky-continuum from instrumental effects (e.g. diffuse light in the wings of strong lines). We aim to obtain, for the first time, a high resolution infrared spectrum deep enough to set significant constraints on the continuum emission between the lines in the H-band. Methods. During the seco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 22 publications
5
67
1
Order By: Relevance
“…In Bland-Hawthorn et al (2004) and Ellis & Bland-Hawthorn (2008) we argued that OH suppression should significantly lower the interline continuum, since some large fraction of typical measured values will be due to scattered OH light, some support for which was found in a detailed study of the NIR night sky spectrum by Sullivan & Simcoe (2012). Oliva et al (2015) stated that following the GNOSIS results we retracted this claim in Ellis et al (2012); in fact the thermal emission in both GNOSIS and PRAXIS have prevented an accurate characterisation of the true interline continuum, and this issue is not yet settled.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In Bland-Hawthorn et al (2004) and Ellis & Bland-Hawthorn (2008) we argued that OH suppression should significantly lower the interline continuum, since some large fraction of typical measured values will be due to scattered OH light, some support for which was found in a detailed study of the NIR night sky spectrum by Sullivan & Simcoe (2012). Oliva et al (2015) stated that following the GNOSIS results we retracted this claim in Ellis et al (2012); in fact the thermal emission in both GNOSIS and PRAXIS have prevented an accurate characterisation of the true interline continuum, and this issue is not yet settled.…”
Section: Discussionmentioning
confidence: 61%
“…The lack of reduction in the interline continuum could be due to the presence of real emission of unknown origin (see e.g. Content 1996;Sullivan & Simcoe 2012;Oliva et al 2015;Nguyen et al 2016), which could be dependent on the observing site, but interpretation is confounded by the low signal-to-noise of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In the J band, no prominent features seem to be missing in the models, and none of the features predicted by the models are missing in the spectra. The long exposure of the M7 star shows a number of sky emission lines from OH airglow (Oliva et al 2015). …”
Section: J Bandmentioning
confidence: 99%
“…Both groups also determined that the rotational temperature of OH(v = 8) was significantly higher than that for OH(v = 9). Figure 1 summarizes the results on OH rotational temperatures reported by Cosby and Slanger (2007), Oliva et al (2015), and Noll et al (2016). Despite some variation, possibly due to the different location, time, and instrument for these measurements, these data sets show a similar trend for the vibrational level dependence of the OH rotational temperatures.…”
Section: Introductionmentioning
confidence: 86%
“…Despite some variation, possibly due to the different location, time, and instrument for these measurements, these data sets show a similar trend for the vibrational level dependence of the OH rotational temperatures. Additional details and the Oliva et al (2015) data set can be found in the original publications as well as in Kalogerakis (2017).…”
Section: Introductionmentioning
confidence: 99%